2021
DOI: 10.20870/oeno-one.2021.55.3.4695
|View full text |Cite
|
Sign up to set email alerts
|

Interannual and spatial variability of grape composition in the Rioja DOCa show better resilience of cv. Graciano than cv. Tempranillo under a warming scenario

Abstract: Weather conditions affect vine development and grape composition, although the response may be different depending on the variety and altitude. Under scenarios of climate change, the knowledge of the relationships between grape composition and climate is therefore important to know the suitability of a given cultivar. In this research, the variability of the grape composition of two red varieties with different phenological timings (Vitis vinifera L. cv. Tempranillo and Graciano) cultivated in Rioja DOCa (Spai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…This trend is amplified at maximum volume stage due to the highest expansion and resulting dilution ( Table 1 ). Morrastel N, also called Graciano in Spain, is a traditional cultivar producing wines rich in polyphenols with moderate ethanol levels (Ramos and Martinez de Toda, 2021). We confirm here, through this study performed at single berry level, that Morrastel N can produce ripe fruit at lower [Hex], i.e.…”
Section: Resultsmentioning
confidence: 99%
“…This trend is amplified at maximum volume stage due to the highest expansion and resulting dilution ( Table 1 ). Morrastel N, also called Graciano in Spain, is a traditional cultivar producing wines rich in polyphenols with moderate ethanol levels (Ramos and Martinez de Toda, 2021). We confirm here, through this study performed at single berry level, that Morrastel N can produce ripe fruit at lower [Hex], i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have been carried out in Rioja DOCa on the main red cultivars (Tempranillo, Grenache and Graciano), 11,26,27 but less attention has been paid to white cultivars, which are also authorized and grown in the area. The results of these previous analysis have shown that the cultivars with earlier phenology may suffer higher impacts in phenology and in grape composition under warming climates than those with later phenology and, given that white cultivars may have earlier timing than red varieties, they could also suffer negative impacts.…”
Section: Introductionmentioning
confidence: 99%